Apolipoprotein A-I attenuates peritoneal fibrosis associated with peritoneal dialysis by inhibiting oxidative stress and inflammation - Lu, Jing; Gao, Jie; Sun, Jing; Wang, Haiping; Sun, Huijuan; Huang, Qian; Zhang, Yao; Zhong, Shuo (Frontiers in Pharmacology, 2023)
Apolipoprotein A-I (apoA-I), 90% of which is present in high-density lipoprotein(HDL), is the main constituent of HDL, has anti-inflammatory and anti-oxidant properties, and has received extensive attention in antiatherosclerosis. Yet little is known about apoA-I 's role in peritoneal dialysis. In this study, by analyzing PD patients (n = 81), we found that decreased apoA/HDL-C ratio is significantly associated with rapid decline in peritoneal function. Further studies were performed in animal experiments to determine the ascendancy of apolipoprotein A-I mimetic peptide (D-4F) on peritoneum, we found that D-4F administration reduced peritoneal fibrosis and peritoneal endothelial mesenchymal transformation (EMT) induced by high glucose peritoneal dialysate, such as N-cadherin, Fibronectin, Vimentin, and α-smooth muscle actin (α-SMA) expression decreased. In mechanism, D-4F can significantly inhibit Smad2/3 phosphorylation, which is the major pathway leading to fibrosis. Furthermore, D-4F treatment inhibited NADPH oxidase and thiobarbituric acid reactive substances (TBARS) expression, increased the activity of certain enzymes, such as superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). Finally, treatment with D-4F inhibits the expression of interleukins-6(IL-6), Interleukin-1β(IL-1β), and tumor necrosis factorα(TNF-α). Taken together, based on the above research evidence, apoA-I and its peptide mimic may regulate the oxidative stress, TGF-β1/Smads 3 signaling pathway and inflammatory response to reduce peritoneal fibrosis due to peritoneal dialysis.